Approaches, methods and models of assessing synergy and market efficiency of integrated production structures at the stages of creation and functioning - D. A. Maximov; D. R. Abbyasova (Путеводитель предпринимателя)
Traditional and modern theoretical approaches and methods of assessing the effect of synergies and market efficiency of integrated production structures at the stages of creation and functioning are considered. The advantages and disadvantages of the most well-known approaches are given and the conclusion about the relevance of developing criteria and models of evaluating the effectiveness of integrated structures, taking into account changes in the target direction of integration processes in modern economy, is made (the transition from cost and profitability criteria to the strategic value criteria), as well as the consequences of creating an integrated group of companies to strengthen the financial framework and diversify the market risk of structural units of the group.